2021
DOI: 10.2196/25060
|View full text |Cite
|
Sign up to set email alerts
|

Conversational Agents as Mediating Social Actors in Chronic Disease Management Involving Health Care Professionals, Patients, and Family Members: Multisite Single-Arm Feasibility Study

Abstract: Background Successful management of chronic diseases requires a trustful collaboration between health care professionals, patients, and family members. Scalable conversational agents, designed to assist health care professionals, may play a significant role in supporting this collaboration in a scalable way by reaching out to the everyday lives of patients and their family members. However, to date, it remains unclear whether conversational agents, in such a role, would be accepted and whether they… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
95
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 69 publications
(104 citation statements)
references
References 101 publications
1
95
2
Order By: Relevance
“…Finally, we found that people who reported a better working alliance with the CA were more adherent to the intervention. This result is in line with studies about regular face-to-face interventions [24,25], digital therapy or treatment [26,27], and automated digital interventions [30,31,32,33,34]. Nonetheless, we did not find an effect of human cues on the reported working alliance with the CA.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Finally, we found that people who reported a better working alliance with the CA were more adherent to the intervention. This result is in line with studies about regular face-to-face interventions [24,25], digital therapy or treatment [26,27], and automated digital interventions [30,31,32,33,34]. Nonetheless, we did not find an effect of human cues on the reported working alliance with the CA.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, in studies that did find an improved working alliance with a CA either the interactions with the agent or the intervention itself were longer compared to those in our study [30,32]. In other studies, although a high working alliance was reported within shorter periods of time, the interactions with the CA followed after introduction by a human healthcare professional [33,34]. It is therefore unclear whether a TCA is less able to build a relationship with the user, or that it requires a longer time or introduction in a face-to-face introduction to do so.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…Out of 19 publications that utilized some mHealth app for patient monitoring, 13 (68.4%) publications [39] , [40] , [41] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] tested the apps which had been developed by publication authors. An interesting app developing model has been presented in one publication [51] .…”
Section: Descriptive Semi-structured and Structured Evidence Synthesesmentioning
confidence: 99%
“…Some of these apps even address disease aspects beyond the conventional patient education or self-monitoring. For instance, three included publications [41] , [45] , [47] targeted family management of pediatric asthma (that is, by actively involving parents or caregivers in the management process) or aimed to foster efficient communication between the family and a healthcare practitioner. Such complex mHealth apps for pediatric asthma were developed by the evidence-informed multidisciplinary teams and benefited from participatory patient contributions (Supplemental Tables 5 and 6).…”
Section: Descriptive Semi-structured and Structured Evidence Synthesesmentioning
confidence: 99%